Pengaruh Persepsi Konstruksi Sosial Kawasan Asia Timur Terhadap Kebijakan Nuklir Korea Utara: Analisis Pada Perubahan Sikap Sikap Korea Utara Menuju Deklarasi Panmunjom - Satria, Arda Vicky; Puspita, Rizky Herdiyanti; Kristiono, Michael J. (Insignia: Journal of International Relations, 2018)
The East Asian stability and security conundrum is partially caused by the unwillingness of North Korea to dismantle its nuclear armaments despite international pressure. However, recent development shows that North Korean Supreme Leader Kim Jong Un has adopted a milder stance as he signed Panmunjom Declaration on 27 April 2018. Using Regional Security Complex Theory (RSCT) prescribed by Buzan and Wæver (2003) as the framework of analysis, this paper argues that the unprecedented change of policy is a part of North Korean response towards the dynamics of regional security in East Asia. In this paper, the four essential variables of East Asia security complex are being analyzed, namely geographical boundary, anarchic structure, polarity and social construction. It is found that there has been a change in North Korea’s perception of the amity-enmity pattern, that is, the social construction of the region. With the switch of perception, North Korea views that there is a lower level of threat posed by the region towards its national interests. As such, North Korea finds that it is beneficial to comply with denuclearization demands in order to gain a better standing with the international community. Keywords: denuclearization, East Asia, Regional Security Complex, North Korea